2006
DOI: 10.1007/s11102-006-0271-4
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of neuroendocrine tumors with somatostatin analogs

Abstract: Neuroendocrine tumors constitute a group of hormone producing tumors originating from neuroendocrine cells in different organs. Most tumors have a low proliferation index measured by Ki67 and the progression of the tumor is slow. However, many patients suffer from endocrine symptoms induced by the hormones produced and released by the tumor cells. For some patients these symptoms can be life- threatening as in midgut carcinoid patients suffering from carcinoid crises with extensive flushes and hypotension or i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
(51 reference statements)
0
7
0
Order By: Relevance
“…Somatostatin receptors are classified into 5 subtypes, and SSTR‐2 is subclassified into 2 variants according to the presence or absence of splicing: SSTR‐2a and SSTR‐2b . SSTR‐2a has been implicated in the inhibition of endocrine hormone secretion, the suppression of growth factor‐induced cell cycle progression, and the induction of apoptosis . Octreotide, a drug that binds with high affinity to SSTR‐2a, was developed to take advantage of these effects .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Somatostatin receptors are classified into 5 subtypes, and SSTR‐2 is subclassified into 2 variants according to the presence or absence of splicing: SSTR‐2a and SSTR‐2b . SSTR‐2a has been implicated in the inhibition of endocrine hormone secretion, the suppression of growth factor‐induced cell cycle progression, and the induction of apoptosis . Octreotide, a drug that binds with high affinity to SSTR‐2a, was developed to take advantage of these effects .…”
Section: Discussionmentioning
confidence: 99%
“…10,11 SSTR-2a has been implicated in the inhibition of endocrine hormone secre-tion, the suppression of growth factor-induced cell cycle progression, and the induction of apoptosis. [11][12][13] Octreotide, a drug that binds with high affinity to SSTR-2a, was developed to take advantage of these effects. 3 Recent studies have demonstrated the therapeutic usefulness of octreotide in patients with unresectable, well differentiated PNETs.…”
Section: Discussionmentioning
confidence: 99%
“…SS analogs are used in the treatment of adult neuroendocrine tumors with good biochemical and clinical response 34. Recently, it has also been shown that the SS analog octreotide LAR has an antiproliferative effect in small intestinal endocrine tumors prolonging the time to progression significantly as compared to placebo treatment 35.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with acromegaly and other neuroendocrine tumors, treatment with SAs can stabilize tumor growth or even induce tumor shrinkage (28,29). With respect to GHRH-secreting carcinoids, data are limited.…”
Section: Discussionmentioning
confidence: 99%